2019
DOI: 10.11604/pamj.2019.34.66.18848
|View full text |Cite
|
Sign up to set email alerts
|

Use of alarm features in predicting significant endoscopic findings in Nigerian patients with dyspepsia

Abstract: IntroductionDyspepsia is prevalent in the community. Guidelines recommend early endoscopy in dyspeptic patients who are older than 55 years, or have alarm features. There is a lack of data on endoscopy in patients with alarm features in Nigeria.MethodsA retrospective study of the endoscopic findings in adults with dyspepsia and alarm features, between August 1st 2017 and July 31st 2018 in Lagos, Nigeria. Data were analysed using Statistical Package for Social Sciences, version 23.0. The sensitivity, specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
0
12
1
2
Order By: Relevance
“…Upper gastrointestinal bleeding, persistent vomiting and odynophagia were specific for significant endoscopic findings. 41 Both the researched studies and the one carried out here, showed that weight loss is the most prevalent alarm signal among patients who undergo upper digestive endoscopies.…”
Section: Hpylorimentioning
confidence: 54%
“…Upper gastrointestinal bleeding, persistent vomiting and odynophagia were specific for significant endoscopic findings. 41 Both the researched studies and the one carried out here, showed that weight loss is the most prevalent alarm signal among patients who undergo upper digestive endoscopies.…”
Section: Hpylorimentioning
confidence: 54%
“…The frequency of gastric masses suspected to be malignant and indeed significant endoscopic lesions was low even in the elderly in this study, despite the frequency of H. pylori infection in the population. Many other studies in Nigeria and overseas have reported similar findings [22,24,25,34]. We know, however, that the outcome of H. pylori infection is an interaction of the virulence of the organism which is determined by its strains, host susceptibility and environmental factors [38].…”
Section: Discussionmentioning
confidence: 65%
“…A study in Atlanta, Georgia also found gastric ulcers more than duodenal ulcers among their patients with dyspepsia [29]. Similarly, Jemilohun et al [24] in Ibadan, Odeghe et al [34], in Lagos, Ugiagbe et al [25], in Benin, all in Nigeria and Agyei-Nkansah et al [11], in Ghana found gastric ulcers to be more common in patients with dyspepsia though these studies did not look at the pattern of the gastritis in their cohorts. However, other studies in Nigeria and Brazil reported duodenal ulcers to be more common than gastric ulcers [22,26,35].…”
Section: Discussionmentioning
confidence: 94%
“…Таким образом, очень важен точный отбор пациентов с более высоким риском развития онкологического заболевания, которые должны быть немедленно отправлены на дополнительное обследование. При наличии «тревожных» симптомов специалисты рекомендуют проводить немедленную эндоскопию всем пациентам, поскольку данные симптомы чаще всего ассоциируются с развитием злокачественных новообразований верхних отделов желудочно-кишечного тракта [33].…”
Section: результатыunclassified